Persaingan Intra-Islam sebagai Tantangan Utama Kampanye Moderasi Beragama di Indonesia: Kasus Komparatif Ahmadiyah dan Syiah - Wasisto Raharjo Jati; Halimatusa'diah Halimatusa'diah (At-Tafkir, 2023)
The intra-Islamic rivalry have been a main challenge in nurturing religious moderation in Indonesia. It basically shows the contestation between each Islamic teachings to shape main narration of religious moderation. That current trend of moderation that led by Sunni has boosted majoritarian perspective among some Muslims and restricted and differentiated minority Muslim groups such as Shia and Ahmadiyya. Consequently, while the current religious moderation has been underway, it unable to accommodate those Muslim minorities. This research aims at analysing the consequences of majoritarian moderation that paradoxically disturbed Ahmadiyya and Shia. Both have been a main proselytization target to be Sunni through violence and persecution because accusation of heresy. By employing data from fieldwork and literatures, this research used qualitative research particularly analytical review. It showed that, the religious moderation cannot bridge in the differentiation Islamic teachings between majoritarian Sunni and Shia/Ahmadiyya. As a result, the violence still underway that affected those Muslim minorities. From this research, it advised to stakeholders hold religious moderation firmly accommodating minorities as part of Muslim society in Indonesia.